Development of the process of determining essential hazardous psychosocial factors of employee stress risk - Bazaluk, Oleg; Tsopa, Vitalii; Cheberiachko, Serhii; Deryugin, Oleg; Nesterova, Olha; Sokurenko, Svitlana; Lozynskyi, Vasyl (Frontiers in Public Health, 2024)
The purpose of the study is to determine the impact of hazardous psychosocial factors on stress among employees when performing production tasks to develop recommendations for reducing their impact. Based on the recommendations of the ISO 45003:2021 standard, a special questionnaire was developed to determine hazardous psychosocial factors that lead to the appearance of worker’s stress, the answers to which were evaluated on a Likert scale with points from 0 to 4. 68 workers (23 men and 45 women) aged 20 to 45 took part in the survey conducted at industrial enterprises of the Dnipro region in May–June 2023. A questionnaire was developed to identify significant psychosocial hazardous factors in personnel at an industrial enterprise, which includes three groups of psychosocial hazardous factors and consists of thirty questions. A ten-step process for managing significant hazardous psychosocial risks is proposed. It was established that women pay more attention to challenges (psychosocial hazardous factors) that are associated with the organization of work (uncertainty at work, lack of breaks due to workload) and social problems (disrespect, disrespect and inattention to employees, unreasonable behavior towards you by leadership); for men, a significant group of hazardous psychosocial factors is—equipment, working environment, hazardous tasks (fear of performing hazardous work; work is associated with a significant risk to life). The novelty consists in the justification of the process of identifying essential psychosocial factors, which will allow managers to systematically monitor the state of mental health of employees, the psychological climate in the organization and respond in a timely manner to expected problems and develop corrective actions to normalize the situation. The process of managing significant hazardous psychosocial risks has been developed, which consists of ten steps and differs from the known procedure of identifying significant hazardous psychosocial factors on a Likert scale, considering the answers of women and men.